In vitro Antioxidant Properties of Novel ?3-Adrenoceptor Agonists Bearing Benzenesulfonamide Fragment - Sichrovska, Lubica; Malik, Ivan; Sedlarova, Eva; Csollei, Jozef; Muselik, Jan (Dhaka University Journal of Pharmaceutical Sciences, 2013)
As an extension of our research, the in vitro antioxidant efficiency of perspective agonists of ?3-adrenoceptors structurally based on the aryloxypropanolamine pharmacophore, chemically 3-{4- [(alkoxycarbonyl)amino]phenoxy}-N-{2-[4-(aminosulfonyl)phenyl]ethyl}-2-hydroxypropan-1-ammonium chlorides, was investigated. The potential of evaluated compounds to reduce relatively stable 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals in the spectrophotometric tests was dependent on the length of the alkyl substituent of alkoxycarbonylamino moiety directly attached to phenyl ring. The elongation of given string was accompanied by the increase in the effectiveness. From the entire analyzed set, the compound containing butoxycarbonylamino group has been able to act most markedly as the reduction agent towards the DPPH radicals showing the percentage of the DPPH reduction (% DPPH) of 11.34±0.02. On the other hand, the tested derivative has shown approximately ninefold decrease in the efficiency compared to applied Trolox standard, a water-soluble analogue of vitamin E, with its %DPPH=95.45±0.02. Dhaka Univ. J. Pharm. Sci. 12(1): 23-28, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16296